1962
DOI: 10.1111/j.1528-1157.1962.tb05155.x
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Abnormalities during Sleep as Related to the Temporal Distribution of Seizures

Abstract: SUMMARY The sleep and awake EEG's of 90 epileptics and 30 normal controls were evaluated. The epileptics were divided into three groups: (1) Nocturnal seizures predominately, (2) Diurnal seizures predominately, (3) Mixed diurnal and nocturnal seizures. Patients with nocturnal seizures showed greater numbers and degrees of abnormalities during sleep EEG's. In patients with diurnal seizures abnormalities appeared about equally in sleep and awake EEG's. The stage of sleep most useful for detecting abnormalities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1965
1965
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…They also noted that seizures were more likely to be activated by sleep or sleep deprivation in patients with IGE than with partial epilepsy. The yield of sleep recordings may be greater in patients with nocturnal seizures versus awake or randomly distributed seizures (White et al, 1962) and in untreated patients with epilepsy (Aguglia et al, 1994).…”
Section: Effects Of Sleep Deprivation On Interictal Epileptiform Discmentioning
confidence: 99%
“…They also noted that seizures were more likely to be activated by sleep or sleep deprivation in patients with IGE than with partial epilepsy. The yield of sleep recordings may be greater in patients with nocturnal seizures versus awake or randomly distributed seizures (White et al, 1962) and in untreated patients with epilepsy (Aguglia et al, 1994).…”
Section: Effects Of Sleep Deprivation On Interictal Epileptiform Discmentioning
confidence: 99%
“…Epilepsy also changes the organization and microstructure of sleep [4]. Since patients with epilepsy have seizures during sleep, this reciprocal interaction has led researchers to investigate the relationship between the pathologic processes underlying seizures and the physiological structures of sleep [5][6][7][8][9]. Arousal or awakening systems that separate sleep and wakefulness are characterized by excitability and increased electrical activity of sensory and motor systems.…”
Section: Introductionmentioning
confidence: 99%
“…34 This is in contrast to an older study by White et al that reported more prominent interictal abnormalities during lighter stages of sleep. 35 The scarcity of abnormal interictal activity during REM sleep is also seen in childhood epileptic syndromes, such as those of West, 36,37 Landau-Kleffner, 38 and Lennox-Gastaut. 39 Although interictal discharges are less prevalent in REM sleep, when they are present they carry more localizing value for the seizure focus.…”
Section: Interictal Dischargesmentioning
confidence: 99%